Space charge effects in fourth-generation light sources: The PETRA IV and SOLEIL II cases - S. A. Antipov; V. Gubaidulin; I. Agapov; E. C. Cortés García; A. Gamelin (Physical Review Accelerators and Beams)
It is a truth universally acknowledged that space-charge effects in ultrarelativistic electron storage rings are irrelevant due to the steep inverse dependence of their strength on the Lorentz factor. Yet, with the push toward the diffraction limit, the state-of-the-art light sources are approaching the point where their emittance becomes so small that the space-charge force can no longer be ignored. In this paper, we demonstrate how space-charge effects influence the injection dynamics, dynamical aperture, and collective beam stability using the example of fourth-generation light sources PETRA IV and SOLEIL II.